Fault Diagnosis Method for Switched Reluctance Machine Drive Systems Using a Switching Signal - Shin, Hye Ung; Lee, Kyo Beum (Journal of Electrical Engineering and Technology, 2019)
This paper presents a fault diagnosis method for switched reluctance machine (SRM) drive systems using a switching signal. This method can detect to the power transistor of power converter which has an open and short circuit. In addition, the information of the short fault switch can be recognized by using signals of the real switch and digital signal processor (DSP). The signals of DSP have some fault patterns, which are analyzed in the power converter, under the fault occurrence situation. The validity of the proposed method is verified by the simulation and experiment using the SRM drive system.
Keywords: Asymmetric bridge converters; Diagnosis methods; Open faults; Short fault; Switched Reluctance Machine; Asymmetric bridge converter; Diagnosis method; Open fault; Power transistor; Short fault; Switched reluctance machine